Geo-spatial variability in soil health of Biwan watershed located at Mewat district of Haryana, India - GURJAR, D S; SUDHISHRI, S; MISHRA, A K; KAUR, R; KHANNA, M (The Indian Journal of Agricultural Sciences, 2018)
A study was carried out to evaluate the geo-spatial variability of soil health parameters in Biwan watershed located in the Mewat district of Haryana in 2012-13. The main objective of this study was to determine spatial variability of selected soil health parameters that influence crop growth and yield. Soil samples (100) with GPS co-ordinates were collected on random basis from Tapkan, Biwan, Shonkh, Palla and Palladi villages of Biwan watershed during pre-monsoon period (May 2012). Soil health parameters such as pH2, electrical conductivity (EC2), organic carbon,Â available NPK and micronutrient (Zn, Fe, Cu and Mn) were analyzed from each sample by the standard methods. The spatial variability maps for different soil health parameters were prepared through GIS software (ArcGIS 9.0). Results indicated that the pH2 (6.0-8.59) and EC2 (<1.0 dS/m) were normal in about 80% of soil samples in watershed area. Comparatively, higher soil salinity was observed in Palladi village. Organic carbon and available nitrogen were low in the soils of whole watershed. The available phosphorous was low in 57% soil samples and rest was in medium. The lower concentration of available phosphorous was in most of the part of watershed, whereas medium concentration was in some part of Biwan and Palladi villages. The available potassium was low in 23%, medium in 67% and high in 10% soil samples. The higher concentration of available potassium was in some parts of Biwan, Shonkh and Palla villages. The Zn concentration was deficient (<0.6 mg/kg) in 70% of soil samples and 30% samples were in sufficient. The higher concentration of Zn was in Tapkan and Palladi villages. 84% soil samples showed the iron (Fe) deficiency. The sufficient Fe concentration was in the scattered patches of the watershed. The Cu and Mn concentrations in most of the soils of Biwan watershed were sufficient. It was concluded from the study that the soil health of Biwan watershed was poor.